Relative elemental concentrations of Ti, V, Cr, Mn, Fe, Ni, Cu, Zn, Ga, Ge, and As of a drill core sample of the Kuruman BIF with microbands measured by the synchrotron-radiation-based μ-XRF - Anyang Ding; Axel Hofmann; Yiliang Li (PANGAEA, 2022)
Modern-day solar cycles due to the solar magnetic field oscillation are well recognized. Owing to the response of Earth extquotesingles climate to solar activity fluctuation, solar cycles in the Phanerozoic eon have been recorded by laminites and fossil tree rings. However, the existence of magnetic cycles within the Sun younger than 3100 million-year-old is still unknown. The deposition of Precambrian banded iron formations (BIFs) reflects the primary productivity of the early ferruginous oceans and is coupled to climatic fluctuations. Here we apply synchrotron-radiation-based μ-XRF with 20 μm interval on a 60 mm long, 2470 million-year-old BIF from the Kuruman Formation, South Africa. The sample is from core GKF01 drilled at the location S 28° 56 extquotesingle 06.0” E 023° 15 extquotesingle 00.0”, as described in Schröder et al. (2006). μ-XRF measurements of the sample were performed at beamline BL15U1 of Shanghai synchrotron radiation facilities (SSRF) with a designed 3.5 GeV electron storage ring and 150-250 mA current. For these measurements, the beam size was controlled at 5 μm exttimes 3 μm (horizontal exttimes vertical). For the XRF measurement, the excitation energy was set at 14.0 KeV, and the dwelling time was set to 5 s. A line of 2972 points was scanned with an interval of 20 μm, perpendicular to the BIF sample extquotesingles microbands. Relative elemental concentrations in counts per second (cps) were obtained by fitting the μ-XRF profiles using PyMca (raw). Segments with systematic measuring anomalies were removed (tail removed). Our spectral analyses of multiple elemental concentration series reveal prominent and consistent 80-year cyclicity, which is best explained as the Gleissberg solar cycle. The result is reported in the article 2470 million-year-old banded iron formation reveals a climatic oscillation consistent with the Gleissberg solar cycle published in Communications Earth & Environment.